Highly efficient isolation and 3D printing of fibroblasts for cultured meat production - Yang, Ruoqing; Fei, Zhuocheng; Wang, Luyi; Tang, Haohao; Sun, Wanqiang; Li, Mei; Lei, Qingzi; Chen, Jian; Guan, Xin (Frontiers in Sustainable Food Systems, 2024)
Fibroblasts are important components of animal tissues such as muscle and skin, as they are the major producers of various matrix proteins. Matrix proteins such as collagen play an important role in meat products by providing unique nutrition, texture, and flavor. Cultured meat is an innovative meat alternative produced by culturing animal cells, but currently, relatively few studies have been conducted using fibroblasts as seed cells for cultured meat manufacturing. In this work, we first developed an innovative digestion-friction method for isolating fibroblasts from porcine skin efficiently and cost-effectively. After optimizing the enzymatic digestion and physical friction conditions, 2.39 ± 0.28 × 105 fibroblasts were obtained from 1 cm2 of porcine skin tissue, which was about 9 times higher than the conventional tissue explant method. In addition, we identified an edible bio-ink composed of gelatin and chitosan that has good printing properties and supports fibroblast adhesion and growth. Furthermore, we fabricated fibroblast-based cultured meat by 3D printing with an initial cell density of 1.0 × 107 mL−1 and evaluated its texture and nutritional properties. This work provides valuable insights and references for introducing fibroblasts into the production of cultured meat that is more comparable to structured animal meat.